Spontaneous proliferation, a response of naïve CD4 T cells determined by the diversity of the memory cell repertoire - Min, Booki (National Academy of Sciences, 2004)
T cell numbers are maintained within narrow ranges in vivo. Introduction of naïve cells into lymphopenic environments results in proliferation and differentiation driven by the recognition of peptide/MHC complexes and by cytokine signaling. This process, often described as homeostatic proliferation, is here referred to as spontaneous proliferation. We show that, although the presence of memory CD4 T cells of broad repertoire efficiently inhibits proliferation/differentiation of naïve CD4 T cells, a memory population of similar size comprised of cells with a repertoire of limited diversity fails to do so, implying that cells of a given specificity prevent responses of cells of the same or related specificity. This finding suggests that the immune system has evolved mechanisms to attain a memory cell repertoire of great diversity independently of foreign antigens.